URGENSI PERJANJIAN PRANIKAH SEBAGAI KESEPAKATAN AWAL PERKAWINAN - Andrean Syah; Ilham Tholatif (Universitas Muhammadiyah Ponorogo, 2022)
The pre-marriage agreement is an agreement made before marriage by a husband and wife, the pre-marriage agreement is considered taboo in society because the agreement should be made during the marriage contract and not many people understand about the pre-marriage agreement, the pre-marriage agreement actually regulates the separation of assets and objects of the prospective husband and wife so that they understand their respective rights and obligations. By law, this marriage agreement is regulated in three laws, namely stipulated in the KUHPER, the Marriage Law, and the Compilation of Islamic Law. The three of them see that the marriage agreement is a form of benefit for the prospective bride and groom so that later it will provide a sense of security and peace because the agreement is binding between the two prospective husband and wife.